Universality of free fall in planck-scale deformed Newtonian gravity - Fabiano, Giuseppe; Frattulillo, Domenico; Pfeifer, Christian; Wagner, Fabian (Physical review, 2025)
The universality of free fall is one of the most cherished principles in classical gravity. Its fate in the quantum world is one of the key questions in fundamental physics. We investigate the universality of free fall in the context of Planck scale modifications of Newtonian gravity. Starting from a doubly-special-relativity setting we take the Newtonian limit to obtain deformed Galilean relativity. We study the interaction between two test particles, subject to deformed Galilean relativity, and a classical, undeformed gravitational source, the Earth. Such an interaction is investigated here for the first time. Considering the two test particles falling freely in the source’s gravitational field, we examine whether the universality of free fall is affected by deformed relativistic symmetries. We show that, in general, the universality of free fall is violated. Remarkably, we find that there exist distinguished models for which the universality of free fall is realized and which predict a specific modification of the Newtonian potential.
Veröffentlicht: 2. Dezember 2025
Gesehen am 27.02.2026